Analisis Pengaruh Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Terhadap Kinerja Karyawan RSPAD Gatot Soebroto Jakarta - Stenly Maramis; Arfhan Prasetyo (Jurnal Sistem Informasi, 2018)
Abstract— The implementation of Hospital Management Information System or SIMRS, is very important nowadays. This is done as an exchange of information from manual process to computerization by using information system. This research is done through literature study, problem formulation, problem solving, data analysis, and then drawing conclusions based on theoretical study. Simple linear regression analysis is an analysis of the relationship of one dependent variable or Y with one independent variable or X. The problem that became the study in this research, is the influence of the application of Hospital Management Information System or SIMRS, to the improvement of Employee Performance. With the test using Simple Linear Regression the result of research shows that the average Y result is 26,02% influence of SIMRS to Performance and b ,direction number or regression coefficient, SIMRS to Performance equal to 0,2%. While in the determinant coefficient test obtained value coefficient determinant or KP, of 4%. This proves that SIMRS has a contribution value to employee performance of only 4%. From the hypothesis test with the calculated r obtained 1.2 results